A Historical Record Of The Reflection On An Individual Vs. Erazm Majewski S Concept Of Man - Szumera, Grażyna (Folia Philosophica, 2000)
The problem of the psychophysical unity of man is one of the most essentia] questions of philosophical anthropology. This peculiar unity of the soul and body is still an enigma for philosophers. While analysing various theories of man’s condition, we notice above all that the human being eludes all kinds of definitions that try to circumscribe him. Man transcends nature and creates a new world, a new reality around himself and in himself, but at no particular moment is he able to say where the line should be drawn between his animal nature and the self-imposed humanity. The problem of the origin of man has also been taken up by Erazm Majewski. The said thinker argues that the way to the so called „superiority” does not necessarily lead through great transformations. It can be connected with conservatism and so it looks also in the case of man's features. Mediocrity then, conservatism, and lack of specialisation of the genus Homo laid, according to Majewski, the foundations for man’s severing his ties with the animal world. The development of man is not a development of an organism, for a cardinal feature of a human being is a certain lock of equilibrium between his physical and psychic aspects. This disequilibrium, however, turns out to be, according to Majewski, unacceptable from a scientific point of view. An equilibrium is maintained, in fact, but it escaped people’s notice, because it was sought in man conceived of a complete biomechanism. The human body alone, however, is not enough for the human psyche, it fails to satisfy all human needs. Nevertheless, in Majewski’s opinion, there is, after all, a state of equilibrium because man has supplemented his innate physicality with artificial tools.